Shiʿi historians in a wahhabi state: identity entrepreneurs and the politics of local historiography in saudi arabia - Matthiesen, T (Cambridge University Press, 2015)
This article analyzes how Saudi Shiʿi historians have adapted tools associated with nationalism to create distinct historical narratives for the Shiʿa of Eastern Arabia. State-sponsored narratives have either left out Shiʿi Muslims or cast them as unbelievers and alien to the Saudi body politic. In contrast, historical narratives written by Shiʿi authors emphasize the Shiʿa's long history of sedentarization, their cultural heritage, and their struggles against foreign occupation. The article is based on fieldwork in Saudi Arabia and a close reading of hundreds of articles and books on local history published mainly since the 1980s. Through the Saudi Shiʿi case, I show that “identity entrpreneurs,” or activists who create, politicize, and profit from identities to further political aims, understand local historiography to be crucial to their overall projects.